The role of l-leucovorin uptake and metabolism in the modulation of 5-fluorouracil efficacy and antifolate toxicity - Peters, Godefridus J.; Kathmann, Ietje; Giovannetti, Elisa; Smid, Kees; Assaraf, Yehuda G.; Jansen, Gerrit (Frontiers in Pharmacology, 2024)
Background: L-Leucovorin (l-LV; 5-formyltetrahydrofolate, folinic acid) is a precursor for 5,10methylenetetrahydrofolate (5,10-CH2-THF), which is important in the potentiation of the antitumor activity of 5-fluorouracil (5FU). LV is also used to rescue antifolate toxicity. LV is commonly administered as a racemic mixture of its l-LV and d-LV stereoisomers. We compared dl-LV with l-LV and investigated whether d-LV would interfere with the activity of l-LV.Methods: Using radioactive substrates, we characterized the transport properties of l-LV and d-LV, and compared the efficacy of l-LV with d-LV to potentiate 5FU-mediated thymidylate synthase (TS) inhibition. Using proliferation assays we investigated their potential to protect cancer cells from cytotoxicity of the antifolates methotrexate, pemetrexed (Alimta), raltitrexed (Tomudex) and pralatrexate.Results: l-LV displayed an 8-fold and 3.5-fold higher substrate affinity than d-LV for the reduced folate carrier (RFC/SLC19A1) and proton coupled folate transporter (PCFT/SLC46A1), respectively. In selected colon cancer cell lines, the greatest enhanced efficacy of 5FU was observed for l-LV (2-fold) followed by the racemic mixture, whereas d-LV was ineffective. The cytotoxicity of antifolates in lymphoma and various solid tumor cell lines could be protected very efficiently by l-LV but not by d-LV. This protective effect of l-LV was dependent on cellular RFC expression as corroborated in RFC/PCFT-knockout and RFC/PCFT-transfected cells.Assessment of TS activity in situ showed that TS inhibition by 5FU could be enhanced by l-LV and dl-LV and only partially by d-LV. However, protection from inhibition by various antifolates was solely achieved by l-LV and dl-LV.In conclusion, in general l-LV acts similar to the dl-LV formulations, however disparate effects were observed when d-LV and l-LV were used in combination, conceivably by d-LV affecting (anti)folate transport and intracellular metabolism.